UJI EFEKTIVITAS SEDIAAN GEL FRAKSI ETIL ASETAT DAUN JAMBU BIJI (Psidium guajava Linn) TERHADAP PENYEMBUHAN LUKA TERBUKA PADA MENCIT (Mus musculus) - Lydia Septa Desiyana; Muhammad Ali Husni; Seila Zhafira (Jurnal Natural, 2016)
Guava leaf has various benefits, one of them is accelerating the healing process of a wound. This study aims to formulate the ethyl acetate fraction into a gel form and test the effectiveness of gel formulation toward open wounds in 16 male mices (Mus musculus) which made excision 1 cm circular full thickness wound on the back of mice parallel with Os. vetebra. The ethyl acetate fraction of guava leaf has been made into concentrations of 5% and 7% with base gel used as negative control and Bioplacenton as positive control. The evaluation towards ethyl acetate fraction gels showed the gels have green-yellow color, guava odor, homogenous, relevant pH to the skin 6,31-6,51, and spread over 2,8-3 cm (stiff gel). The gels were applied onto the wounds twice a day for about 21 days. The observation was conducted every day towards the scab formation day, scab chipped day, and wound healing day. The data were analyzed statistically using one way ANOVA then continued with Tukey test. The average day for scab formation, scab chipped, and wound healing process, successively are in the negative control i.e. 6,50 ; 13,50 ; 20,25, then positive control of  3,75 ; 11,00 ; 17,25, for gel with 5% concentration,  3,75 ; 9,75 ; 16,50, and gel with 7% concentration,  4,50 ; 12,00 ; 18,25. The statistical result showed that the ethyl acetats fraction  could accelerate the scab formation (p0,05) and the open-wound healing (p0,05) in mice than the control negative (p0,05), but not in the scab exfoliation (p0,05). Gel concentration 5% accelerated faster in forming the scab, flaking off the scab, and  healing the wound compared with the gel concentration of 7%.